ISU KESETARAAN GENDER DALAM OPTIK FEMINIST JURISPRUDENCE DAN IMPLEMENTASINYA DI INDONESIA - Heri Setiawan; Steven Ouddy; Mutiara Girindra Pratiwi (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2018)
The feminists are of the view that history is written from the point of view of men and does not voice the role of women in making history and forming the structure of society. The history written by men has created a bias in the concept of human nature, gender potential & ability, and in community settings. Language, logic and legal structure are created by men and strengthen the value to men. Feminists challenge and dismantle the belief or myth that men and women are so different, that certain behaviors can be distinguished on the basis of gender differences. Gender according to feminists is created or socially shaped not biologically. Sex determines physical appearance, reproductive capacity, but does not determine psychological, moral or social characteristics. This difference in responsibility between genders then results in